Dampak COVID19 Pada Kesiapan Teknologi dan Penerimaan Teknologi di Kampus - Panday, Rorim (Jurnal Kajian Ilmiah, 2020)
Covid-19 is currently in Indonesia for more than 5 months. To prevent this disease becoming widespread, various strategies have been carried out, among others, by doing Lock Down and large-scale social restrictions. Community activities are affected. By relying on communication technology and IT including the Internet, people can still do activities even with limitations. Likewise, Higher Education got limited activities. For this reason, all teaching and learning activities used an online system known as e-learning. This paper conveys various activities on campus and its constraints during the covid-19. In general, the constraints aside from technological facilities are also obstacles from the academic community in matters relating to technology readiness and technology acceptance, which are delivered descriptively. Keywords: Covid19, e-learning, technology readiness, technology acceptance Abstrak Covid-19 tengah melanda Indonesia saat Ini sudah 5 bulan lebih. Untuk mencegah wabah ini menjadi luas maka dilakukan berbagai strategi antara lain dengan melakukan Lock Down dan pembatasan social skala besar. Kegiatan masyarakat menjadi terpengaruh. Dengan mengandalkan teknologi komunikasi dan IT diantaranya Internet, masyarakat masih dapat melakukan Kegiatan walaupun dengan keterbatasan. Demikian juga dengan Perguruan tinggi, mengalami keterbatasan kegiatan. Untuk itu segala Kegiatan belajar mengajar menggunakan system daring yang dikenal dengan e-learning. Makalah ini menyampaikan macam-macam kegiatan di kampus dan kendalanya dalam masa covid-19. Secara umum kendalanya selain fasilitas teknologi juga kendala dari civitas akademika dalam hal yang terkait dengan kesiapan teknologi dan penerimaan teknologi, yang disampaikan secara diskriptif. Kata kunci: Covid19, e-learning, kesiapan teknologi, penerimaan teknologi